Second-line Endocrine Therapy of Hormone Receptor-positive/HER2- negative Advanced Breast Cancer: A Systematic Review and Network Meta-analysis - Wang, Tianzhuo; Shen, Guoshuang; Li, Jinming; Huo, Xingfa; Wang, Miaozhou; Liu, Zhen; Zhao, Fuxing; Ren, Dengfeng; Zhao, Jiuda (Current Cancer Drug Targets, 2023)
Background: The optimal second-line therapy for hormone receptor-positive (HR+)/ human epidermal growth factor receptor 2 negative (HER2−) advanced or metastatic breast cancer is yet to be established. Therefore, we conducted a network meta-analysis (NMA) of marketed drugs to compare their efficacy. Methods: We searched the literature in PubMed, Embase, Web of Science databases, and the main international conferences in the past 5 years to find phase III clinical trials on drugs available in the market. Network meta-analysis of progression-free survival (PFS), overall survival (OS), and the objective response rate (ORR) was performed using R software. The efficiency of treatment options was compared using hazard ratios and 95% credibility intervals. Results: Overall, 12 studies with 6120 patients were included in the analysis. In an indirect comparison of the five regimens, cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) plus 500 mg fulvestrant (Ful500) gave the best PFS results; palbociclib ranked first with a surface under the cumulative ranking (SUCRA) of 94.99%, followed by mammalian target of rapamycin inhibitor (mTORi) plus everolimus (SUCRA=73.07%), phosphoinositide 3-kinase inhibitor (PI3Ki) plus Ful500 (SUCRA=66.73%), Ful500 alone (SUCRA=44.55%), and histone deacetylase inhibitor (HDACi) plus exemestane (SUCRA= 43.49%). However, no significant difference was found in the PFS rates of CDK4/6i, mTORi, and PI3Ki. For OS, CDK4/6i plus Ful500 ranked first; the SUCRA of ribociclib, abemaciclib, and palbociclib were 86.20%, 83.98%, and 78.52%, respectively. Alpelisib plus Ful500 (SUCRA=66.91%) ranked second but was not statistically different from CDK4/6i. The mTORi plus everolimus group had the best ORR (SUCRA=88.73%). In terms of safety, 81.56% of patients in the tucidinostat plus exemestane regimen developed neutropenia, suggesting strong hematological toxicity; 13.40% of patients developed grade 3-4 diarrhea after using abemaciclib plus Ful500. Conclusion: For second-line endocrine therapy in HR+/HER2− advanced/metastatic breast cancer, CDK4/6i is a better choice than mTORi, PI3Ki, HDACi, and Ful; it shows good PFS and OS outcomes and a low probability for serious adverse events.
Keywords: Metastatic breast cancer